Analisa Penjualan Sarang Burung Walet Dengan Metode Naïve Bayes - Rhama Aulia Febrian; Dendi Sugito; Michael Albert Kristiyanto (Jurnal ICT : Information Communication & Technology, 2019)
The method used in the SPK research of swiftlet nest sales uses the naïve bayes method because complex problems can be easily simplified so as to obtain a decision making process by providing a comparison value of each criterion to determine the criterion value from the sales of swiftlet nests so that we can find swiftlet nests. what sells the best using the naïve bayes method. From the data set that we have obtained, there is a value that contains about how the sale value of swiftlet nests that are sold with the highest selling value, observation of cases that we process this further, should in the future provide quality sales value and can be detailed by doing calculations which is very appropriate, so that each swiftlet nest sale can still be controlled and be detailed by every business person in the business field. In the data set that we process in swallow's nest sales data every 2 months has three steps in the naïve bayes method in order to find results in every nest sale. 1. looking for Prior Proba values, 2 Calculating the Likelihood value for each attribute, 3 calculating the Likelihood value for each attribute so that it can find the final value on each calculation that can be used as the final value for each sale.